Indonesian industrialization: A latecomer adjusting to crises - Haryo Aswicahyono; Hal Hill; Dionisius Narjoko (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper examines Indonesia's industrialization performance and policies, including its latecomer status, its generally rapid growth since the mid-1960s, its pronounced policy and performance episodes, and its ambivalent embrace of globalization. Particular attention is accorded to the deep economic-political crisis of 1997 - 98 and its aftermath, with the benefit of a rich, firm level database. The crisis resulted in slower industrial growth, less industrial mobility, and sluggish formal sector employment growth. We also consider some of the general analytical and policy implications for developing country industrialization from the Indonesian experience.
Keywords: D22; J21; L60; O14; 330; Indonesia; industrialization; economic crises; jobless growth; Industrialisierung; Industrialisierungspolitik; Indonesien